2017
DOI: 10.4314/tjpr.v16i4.26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of combined ulinastatin and continuous renal replacement therapy on management of severe sepsis with acute kidney injury

Abstract: Purpose: To explore the effect of a combination of ulinastatin and continuous renal replacement therapy (CRRT) for the treatment of severe sepsis with acute kidney injury (SAKI Results: Levels of interleukin-6 (IL-6), tumor necrosis factor α (TNFα), serum C-reactive protein (CRP), procalcitonin (PCT), malondialdehyde (MDA), cystatin, blood urea nitrogen (BUN), prothrombin time (PT), activated partial thromboplastin time (APTT), serum creatinine (SCr) and urinary kidney injury molecule-1 (Kim-1) in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The effect of UTI on kidney functions was consistent with a previous study, which found that UTI treatment improved kidney functions in patients with acute kidney injury induced by severe sepsis by significantly lowering BUN and serum creatinine levels [ 14 ]. Previous research on the effect of UTI on blood glucose levels has yielded conflicting results.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of UTI on kidney functions was consistent with a previous study, which found that UTI treatment improved kidney functions in patients with acute kidney injury induced by severe sepsis by significantly lowering BUN and serum creatinine levels [ 14 ]. Previous research on the effect of UTI on blood glucose levels has yielded conflicting results.…”
Section: Discussionsupporting
confidence: 90%
“…We extracted the data from 12 studies (Fang and Chen, 2005; Shao et al, 2005; Ni et al, 2008; Sung et al, 2009; Tang, 2013; Wu et al, 2013b; Karnad et al, 2014; Chen et al, 2015; Choudhuri et al, 2015; Wu et al, 2016; Fang and Zhao, 2017; Pavan Kumar Rao et al, 2017) and 1110 participants were classified into two groups to assess all-cause mortality. All-cause mortality was significantly lower in the UTI group than in the control group (OR = 0.48, 95% CI [0.35–0.66], p < 0.00001), and heterogeneity in the results was not observed (x 2 = 12.57, p = 0.37, I 2 = 13%).…”
Section: Resultsmentioning
confidence: 99%
“…We obtained the related data from eight studies (Fang and Chen, 2005; Shao et al, 2005; Jiang et al, 2006; Wang et al, 2007; Tang, 2013; Wu et al, 2013b; Chen et al, 2015; Fang and Zhao, 2017) (402 participants in two groups) to analyze the serum levels of IL-6. The serum level of IL-6 at the time of hospital admission was not different between the UTI and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 – 16 ] It is characterized by rapid onset, rapid change of disease condition, and high fatality rate. [ 17 ] Severe pneumonia is the leading cause of death among children. [ 18 ] Severe pneumonia is common in pathogenic bacteria infection, and pulmonary infection is gradually aggravated due to unreasonable use of antibiotics and patients’ own physical factors, thus causing damage to multiple organs throughout the body [ 19 ] and developing into severe pneumonia.…”
Section: Discussionmentioning
confidence: 99%